Issues relating to the practice of Bai' Bithaman Ajil (BBA) in Malaysia : a critical analysia / Eka Nurfateha Mohd Rose Dzidan - Mohd Rose Dzidan, Eka Nurfateha (Academy of Contemporary Islamic Studies (ACIS), 2016)
Islamic financial industry experienced a massive growth over the last few years. Malaysia is one of the countries that show an amazing progress in this field. The current global financial crisis made some believe that the time has come for the Islamic finance to assume a greater role in the world of financial. Thus, a big step has been taken by introducing some Islamic finance products that can be applied well in this country in accordance with the Shari’ah principle. One of the most preferred kinds of Islamic financing in Malaysian Islamic Banking Industry is Bay' Bithaman Ajil or better known by its acronyms BBA. This is because of the easiness of this product to be compared to the others but in the same time, it is also considers as the most debated type of facility in terms of its validity and Shari’ah compliance. This paper discusses the application of BBA in Malaysia and some possible issues that rise in the practice of this contract. This paper also attempts in suggesting the ways to overcome the disputable issues. This is to give benefit to the customer yet to the society so that, there will be no dispute happen in dealing with this contract. Library research and interview are the methods used in conducting this paper. Interview is conducted at Bank Islam Malaysia Berhad branch University Teknologi Mara.